Physicochemical properties and heavy metals characteristics of building ceramsites with oil-based drilling cutting residues - Xiong, Deming; Wang, Chaoqiang (Scientific reports, 2025)
Oil-based drilling cutting residues (OBDCRs) are among the primary solid wastes generated during shale gas exploration and development. Utilizing existing equipment to transform OBDCRs into ceramsites appears to be a feasible and resource-efficient approach. In this study, building ceramsites were prepared with OBDCRs incorporating with fly ash (a byproduct of coal combustion) as raw materials. The aim was to comprehensively and systematically investigate physicochemical properties and characteristics of heavy metals (HMs) in the ceramsites. Research shows that building ceramsites can indeed be prepared using OBDCRs, which exhibit good comprehensive properties and strong resistance to acid/ alkali. The main HMs found in ceramsite are barium (Ba), chromium (Cr), nickel (Ni), lead (Pb), arsenic (As), cadmium (Cd), and mercury (Hg). During the calcination process, these OBDCRs, along with fly ash and foaming agent, underwent mutual melting, resulting in the formation of glass, anorthite and mullite. These newly formed phases effectively encapsulated HMs, resulting in varying degrees of enrichment of HMs such as As, Ba, Pb, Cr, and Ni, except for Cd and Hg. However, the leaching toxicity of these HMs in the ceramsite was significantly lower compared to that of the original OBDCRs. Further analysis revealed a significant increase in the proportion of Fe–Mn Oxides and Organic Matter in HMs such as Cr, Ni, As, Cd, and Pb, while the proportion of Exchangeable and Carbonates forms decreased markedly. This trend clearly demonstrated that the calcination process modified the physical and chemical properties of the ceramsite, and effectively stabilized HMs, i.e., migrated from an active state to a more stable form.